2006
DOI: 10.1007/s00449-006-0094-8
|View full text |Cite
|
Sign up to set email alerts
|

Should human chondrocytes fly? The impact of electromagnetic irradiation on chondrocyte viability and implications for their use in tissue engineering

Abstract: A significant logistic factor as to the successful clinical application of the autologous tissue engineering concept is efficient transportation: the donor cells need to be delivered to tissue processing facilities which in most cases requires air transportation. This study was designed to evaluate how human chondrocytes react to X-ray exposure. Primary cell cultures were established, cultured, incubated and exposed to different doses and time periods of radiation.Subsequently, quantitative cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…One‐time exposure of EMF caused little long‐term changes in chondrocyte cells in vitro in terms of improving cartilage tissue repair. Several groups have reported that EMF did not alter extracellular matrix production of cultured chondrocytes 16, 17, 20, 33. Type I collagen, which was used as the matrix in this project, composes only a small portion in articular cartilage and does not have the desired mechanical property similar to natural cartilage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One‐time exposure of EMF caused little long‐term changes in chondrocyte cells in vitro in terms of improving cartilage tissue repair. Several groups have reported that EMF did not alter extracellular matrix production of cultured chondrocytes 16, 17, 20, 33. Type I collagen, which was used as the matrix in this project, composes only a small portion in articular cartilage and does not have the desired mechanical property similar to natural cartilage.…”
Section: Discussionmentioning
confidence: 94%
“…Although many studies highlighted potential EMF application in cartilage repair, between study differences in the species, cell type, EMF characteristics, and exposure protocols, and cell culture media selection and the serum content, imposed considerable difficulties to generalization with respect to cause and effect 17–19, 33, 34. Elliott et al34 found EMFs generated by coils oriented vertically and horizontally had different effects on chondrocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have evaluated the potential of pulsed electromagnetic fields on cartilage repair and chondrocyte bioactivity, but definitive conclusions and recommendations cannot be made due to different cell types, tested species, PEMF characteristics, exposure protocols, cell culture media selection, and serum content of these previous investigations. 27,[29][30][31][32][33] Although Nicolin et al 34 and De Mattei et al 35 reported that PEMF had a significant effect on increasing chondrocyte proliferation and producing extracellular matrix, other studies demon-…”
Section: Discussionmentioning
confidence: 99%